PENGARUH E-SERVICE QUALITY, E-WORD OF MOUTH, DAN E-CUSTOMER TRUST TERHADAP REPURCHASE INTENTION PENGGUNA E-COMMERCE - Mahendra, Adiyatma Rozan; Mugiono (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Massive development especially in technology will remain in Indonesia. Such advancement drives internet-based service providers, in this case Gojek Indonesia, to make use of technological innovations. In order to stay in the competition, the company has to encourage their customers to make repurchases through their offers. The goal of this research is to identify the effects of e-service quality, e-word of mouth, and e-customer trust on the repurchase intention of Gojek users with productive age in Malang city. Using non-probability sampling method and purposive sampling technique with the criteria of Gojek user with the minimum age of 17 years living in Malang city who have made at least two purchases through the application, 115 people were selected as the respondents of this explanatory research. The results of the questionnaire were preliminary assessed using validity and reliability tests, while classical assumption test was conducted prior to the multiple linear regression analysis in SPSS version 25. This study finds that e-service quality, e-word of mouth, and e-customer trust partially have positive and significant effects on repurchase intention. This fact indicates that increases in e-service quality, e-word of mouth, and e-customer will be followed by higher repurchase intention among Gojek users in Malang city.